1982
DOI: 10.1161/01.hyp.4.4.494
|View full text |Cite
|
Sign up to set email alerts
|

Overnight urine collections to estimate sodium intake.

Abstract: SUMMARY This study was undertaken to formulate reliable confidence limits for the relationship between nocturnal and 24-hour urine sodium (Na) excretion for use in population compliance studies. Urine excretions were measured in 12 white and 12 black men at three levels of sodium (Na) intake (10, 200, and 400 mEq/day) for 7 days. Nocturnal Na, chloride (Cl), and Cl determined by titrator stick were all highly correlated (r2= 0.86, p < 0.001) with 24-hour U N .V. No significant difference could be attributed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 0 publications
0
35
1
Order By: Relevance
“…Additional contributors would be inter-individual differences in renal function, interval between dinnertime and bedtime, antidiurenic hormone (ADH) function and in sweating. Some studies have demonstrated good correlations between overnight urinary salt and 24-h urinary salt, [18][19][20] whereas others found an absence of correlation 28,29 and some suggest seven or 14 measurements are needed to replace 24-h urine collection. 19,30 Urinary salt excretion is affected not only by the previous day's salt intake, but also by the salt intake of the previous 3 or 4 days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additional contributors would be inter-individual differences in renal function, interval between dinnertime and bedtime, antidiurenic hormone (ADH) function and in sweating. Some studies have demonstrated good correlations between overnight urinary salt and 24-h urinary salt, [18][19][20] whereas others found an absence of correlation 28,29 and some suggest seven or 14 measurements are needed to replace 24-h urine collection. 19,30 Urinary salt excretion is affected not only by the previous day's salt intake, but also by the salt intake of the previous 3 or 4 days.…”
Section: Discussionmentioning
confidence: 99%
“…18-20 K Salt titrator sticks and tapes are known as simple method to detect the concentration of salt in overnight urine. 18,21 K Sensitivity and resistance to the effects of sodium were evaluated by the degree of BP change between high-salt diet and low-salt diet. [22][23][24] What this study adds K A new simple method to monitor daily salt intake was developed.…”
Section: Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…The ratio of mean 24-h to mean overnight excretion of sodium observed in HCP hypertensives was also lower than similar ratios derived from published data for young adults, normotensives, and borderline hypertensives. [53][54][55][56][57][58] Given the ages of HCP participants (41-80 years), it was not clear whether the observed reversal of diurnal patterns of sodium and water excretion was associated with hypertension per se, or reflected decline of renal functional capacity with age, since age appears to modify factors which determine renal sodium handling, including glomerular filtration rate and renal haemodynamics. 59 Furthermore, in one study, persons over age 40 had a lower ratio of mean 24-h to mean overnight excretion of sodium than persons under 40.…”
Section: Discussionmentioning
confidence: 99%